Performance Evaluation of Dynamic Absorbers Based on Randy Fox and Dunkerley Methods / Syafirah A. Samat ...[et al.] - A. Samat, Syafirah; Mat Isa, A.A.; Anuar, M. Azhan (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
Dynamic Absorber (DA) application is the method used to avoid resonance in a vibrating system. In practice, many types of DA are utilized such as active and passive DA and it depends on the cost and environmental conditions. Designers/ engineers select DA parameters and model the absorber before it is implemented and tested to the main system. Hence, it will be beneficial to have tools or templates for fast and effective selection of DA. This paper will discuss the selection parameters of a passive DA based on templates derived from Dunkerley Method (DM) and Randy Fox Method (RFM) and its accuracy is verified experimentally. It is observed that in this case, DA has reduced the vibration amplitude significantly. Furthermore, the results show the RFM absorber has performed better than the DM absorber. This study enables verification of the effectiveness of DA to tackle resonant problems. In the future, these GUI templates could be helpful for industrial application with vibrating problems.